2002
DOI: 10.1074/jbc.m201672200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biologically Active Sequences in the Laminin α4 Chain G Domain

Abstract: Laminins are a family of trimeric extracellular matrix proteins consisting of ␣, ␤, and ␥ chains. So far five different laminin ␣ chains have been identified. The laminin ␣4 chain, which is present in laminin-8/9, is expressed in cells of mesenchymal origin, such as endothelial cells and adipocytes. Previously, we identified heparin-binding sites in the C-terminal globular domain (G domain) of the laminin ␣4 chain. Here we have focused on the biological functions of the laminin ␣4 chain G domain and screened a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
60
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…However, this glycoprotein may influence valve cell types differently. In vivo and in vitro studies have shown that laminin interacts with endothelial and epithelial cells, and can help maintain physiological functionality of the cells [97,100,101]. However, VICs cultured on laminin have been found to support high quantities of calcific nodule formation in the presence of TGF-β, when compared to subendothelial ECM components collagen type I and fibronectin [19,102].…”
Section: The Basement Membrane Supports Valve Endothelial Cells and Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, this glycoprotein may influence valve cell types differently. In vivo and in vitro studies have shown that laminin interacts with endothelial and epithelial cells, and can help maintain physiological functionality of the cells [97,100,101]. However, VICs cultured on laminin have been found to support high quantities of calcific nodule formation in the presence of TGF-β, when compared to subendothelial ECM components collagen type I and fibronectin [19,102].…”
Section: The Basement Membrane Supports Valve Endothelial Cells and Amentioning
confidence: 99%
“…In addition to their structural contributions to the basement membrane, laminins are essential for proper biological activity. These glycoproteins have been shown to promote cell adhesion, migration, differentiation, and maintenance of cellular phenotype [94,97,98]. Dysfunction in laminin expression has been linked to diseases with improper tissue formation such as muscular dystrophy, epidermolysis bullosa, and various nephritic syndromes [94,99].…”
Section: The Basement Membrane Supports Valve Endothelial Cells and Amentioning
confidence: 99%
“…The A3G75 site (KNSFMALYLSKG, human laminin ␣ 3 chain 1411-1422) promoted syndecan-2-and syndecan-4-mediated cell attachment and neurite outgrowth (29,30). The A4G82 (TLFLAH-GRLVFM, mouse laminin ␣ 4 chain 1514 -1525) sequence showed heparin binding and cell attachment activity (31,32). These active sequences are in the homologous region of the LG4 modules of the ␣ 3 and ␣ 4 chains.…”
mentioning
confidence: 99%
“…The crystal structure of the laminin ␣ 2 LG5 module has been prepared and found to consist of 14 ␤ strands (A-N strands) (35). The homologous regions of A3G75 and A4G82 are located on the connecting loop region between the E and F strands (14,29,30,32). Additionally, mutagenesis analysis using recombinant LG4 proteins with serine or alanine substitutions of basic residues (Lys 1421 and Arg 1423 , human laminin ␣ 3 chain; His 1519 and Arg 1521 , mouse laminin ␣ 4 chain) in the E-F loop regions suggested that the loop regions are critical for the biological activity of the recombinant proteins (29,31).…”
mentioning
confidence: 99%
“…By analogy with the identification of the Arg-Gly-Asp (RGD) cell-adhesive motif in fibronectin, many attempts have been made to identify specific sequences mimicking the integrin binding activity of laminins. However, neither recombinant fragments of the G domain nor synthetic peptides modeled after the sequences in the G domain have shown any significant cell-adhesive activity comparable with that of intact laminins (15)(16)(17)(18). Previously, we found that deletion of the LG4-5 modules did not compromise the ability of laminin-511 4 (␣5␤1␥1) to bind ␣3␤1/␣6␤1 integrins, but further deletion up to the LG3 module resulted in the loss of its integrin binding ability (19).…”
mentioning
confidence: 99%